2022
DOI: 10.3390/ijms23094835
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity, Colonisation by Fibroblasts and Antimicrobial Properties of Surgical Meshes Coated with Bacterial Cellulose

Abstract: Hernia repairs are the most common abdominal wall elective procedures performed by general surgeons. Hernia-related postoperative infective complications occur with 10% frequency. To counteract the risk of infection emergence, the development of effective, biocompatible and antimicrobial mesh adjuvants is required. Therefore, the aim of our in vitro investigation was to evaluate the suitability of bacterial cellulose (BC) polymer coupled with gentamicin (GM) antibiotic as an absorbent layer of surgical mesh. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…One study using osteoblasts and fibroblasts found no cytotoxicity when cells were seeded on a BC‐coated surgical mesh 96 . Another study using rabbit bone marrow mesenchymal stem cells found a viability rate of 94% when seeded on BC 97 . In both studies, surgical meshes were fully covered by BC, meaning that cells were not in direct contact with the implants but rather with the BC.…”
Section: Bacterial Cellulose (Bc) Physicochemical Propertiesmentioning
confidence: 99%
“…One study using osteoblasts and fibroblasts found no cytotoxicity when cells were seeded on a BC‐coated surgical mesh 96 . Another study using rabbit bone marrow mesenchymal stem cells found a viability rate of 94% when seeded on BC 97 . In both studies, surgical meshes were fully covered by BC, meaning that cells were not in direct contact with the implants but rather with the BC.…”
Section: Bacterial Cellulose (Bc) Physicochemical Propertiesmentioning
confidence: 99%
“…[126][127][128] In recent years, the application of bacterial cellulose (BC) in the fabrication of advanced AWHPMs has been significantly attractive. [61,129,130] BC produced by bacteria (e.g., Komagataeibacter xylinus X-2 [59] ) has a linear structure comprised of beta-1,4-glucan chains. [129,130] Some studies have shown that exhibiting unique crystallinity and cohesion levels, BC-based patches provided a safe and efficient pathway in AWR, compared to cellulose.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Development of appropriate drug delivery systems for conventional (e.g., antibiotics, antiseptic molecules) and unconventional antibiofilm agents is another direction to follow assiduously to make progress in our ability to control biofilms. Two articles of the collection deal with the use of bacterial cellulose (BC) as a delivery system for antibiofilm active molecules [ 9 , 10 ]. Such biopolymers are produced by numerous genera of bacteria and are emerging as promising candidates for the delivery of active pharmaceutical compounds due to their favorable physical, chemical and biological properties that include flexibility, high porosity, hydrophilic nature, small size, high polymerization degree, easy modification, biodegradability, and biocompatibility [ 18 ].…”
mentioning
confidence: 99%
“…Such biopolymers are produced by numerous genera of bacteria and are emerging as promising candidates for the delivery of active pharmaceutical compounds due to their favorable physical, chemical and biological properties that include flexibility, high porosity, hydrophilic nature, small size, high polymerization degree, easy modification, biodegradability, and biocompatibility [ 18 ]. In the first article of the collection, the Authors chemisorbed BC with several antiseptic molecules, commonly used for the management of biofilm-associated wound infections, and evaluated the anti-biofilm activity of such dressings against a vast collection of strains involved in wound infections [ 9 ]. High levels of antibiofilm activity were recorded, especially when BC was functionalized with iodine povidone whose action was higher than that of a conventional broadly applied silver dressing, at least against some of the bacterial species tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation